The impact of the usage of social networking sites among youth at Bandaraya Melaka public university / Aimi Raihana Rosli and Nur Fatin Fatihah Ahmad Ruzi - Rosli, Aimi Raihana; Ahmad Ruzi, Nur Fatin Fatihah (Faculty of Administrative Science and Policy Studies, 2014)
The purpose of this research is to identify the impact of the usage of social networking sites on youth at Bandaraya Melaka Public University. This study intends to identify the impact of the usage of social networking sites on youth at Bandaraya Melaka on four (4) areas that are student attitude, student time, student academic performance and student relationship. For the purpose of this study, the researchers used stratified sampling as the sampling technique through the questionnaires. In conducting the research, the researchers used 357 respondents, that are from Universiti Teknologi Mara Bandaraya Melaka and Universiti Teknikal Malaysia Melaka (UTEM) Kampus Bandar. There are various methods and analysis are used to analyse the data collected from the questionnaires. Various method and analysis had been applied to do data analysis such as reliability analysis, assessing normality, correlation and central tendency. Upon completion of the research, by applying correlation test, researchers found that all the 4 areas give impact on the usage of social networking sites among youth at Bandaraya Melaka public university. The final result showed that, among the four (4), student attitude as the most significant factor in the impact of the usage of social networking sites among youth at Bandaraya Melaka public university.